Pentecostal movements, Islam and the contest for public space in Northern Nigeria - Ojo, Matthews A. (Islam and Christian-Muslim relations, 2007)
The article considers the changing relationship between independent Pentecostal and charismatic groups and radical Islamic movements in Northern Nigeria between the 1970s and the early years of the twenty-first century. All these groups, be they Christian or Muslim, represent a new dimension in religious fundamentalism in contemporary Nigeria. In spite of being internal revivalist groups within their respective religious traditions, they reflect negative attitudes toward each other. Their relationship has been marked by continuous competition for public space. In the late 1980s and early 1990s, the demonization of Islamic groups was a feature of Pentecostal discourse. Through their involvement in political activities under the umbrella of the Christian Association of Nigeria (CAN), evangelicals and Pentecostals developed a common front in the face of Muslim fundamentalism.